Measuring web service security in the era of Internet of Things. (February 2018) - Zhou, Bo; Zhang, Quan; Shi, Qi; Yang, Qiang; Yang, Po; Yu, Yinyan
Abstract : Hihglights: Comprehensive study on how to measure web service security. Solution uniforms fuzzy terms in SLA to calculate an overall security value. A practical solution allows direct comparison and ranking of web services. Tested by assessing the security features offered by major cloud services in market. Graphical abstract: Abstract: Technologies such as Internet of Things allow small devices to offer web-based services in an open and dynamic networking environments on a massive scale. End users or service consumers face a hard decision over which service to choose among the available ones, as security holds a key in the decision making process. In this paper a base linguistic evaluation set is designed, based on which all the other fuzzy term sets that used for describing security attributes are uniformed and integrated for calculating an overall security value of the services. This work, to the best of our knowledge, is the first practical solution to offer direct comparisons and rankings of network services based on multiple security attributes such as confidentiality, availability, privacy and accountability. We analysed four major cloud service platforms to illustrate the proposed approach.